Association between Serum Uric Acid and Blood Glucose Level in Diabetic and Non-diabetic Patients - Pandey, Rachana; Humagain, Sanjaya; Risal, Prabodh; Yadav, Rahul Kumar; Pokhrel, Buddhi Raj (Nepal Medical College Journal, 2022)
Uric acid increases insulin resistance; likewise, hyperinsulinemia increases uric acid concentration, and both are global health problems. This study is conducted to find the association between serum uric acid and blood glucose level. This was a cross-sectional study conducted in the Department of Biochemistry and Internal Medicine at Dhulikhel Hospital, Nepal, for a duration of six months (September 2021 - February 2022). A total of 130 diabetic patients who consented were compared with 130 non-diabetics by using non-probability convenient sampling technique. Ethical clearance was taken from the Institutional Review Committee-Kathmandu University School of Medical Sciences. Venous blood was collected and fasting blood glucose, post-prandial blood glucose, and serum uric acid were measured. Data were analyzed in the Statistical Package for Social version 16.0. Analytical data were compared using Mann Whitney U test, and Spearman correlation was performed to correlate numerical parameters. Statistical significance was defined as a two-sided p-value of less than 0.05. The median of serum uric acid level was significantly higher in diabetics than non-diabetics; the level of fasting and post-prandial blood glucose positively correlated with serum uric acid (p<0.05). Hyperuricemia was more in diabetics than non-diabetics (p<0.05). Serum uric acid level increased with the increase in age and duration of diabetes.